QUO VADIS CRIMINAL PROCEDURAL LAW IN INDONESIA AFTER THE ENACTMENT OF LAW NUMBER 1 OF 2023 CONCERNING THE CRIMINAL LAW CODE - Hasbullah; Pratiwi, Dian Ayu (International Journal of Social Service and Research, 2025)
The criminal law reform in Indonesia was initiated through the enactment of Law No. 1 of 2023 concerning the Criminal Code, which replaces the provisions of the 1946 Criminal Code. One significant change relates to the prosecution process, particularly concerning the circumstances under which prosecutorial authority may lapse. This study aims to examine the circumstances that cause the termination of prosecutorial authority and to analyze the regulation of the prosecution process following the implementation of the new Criminal Code. A normative juridical method was employed, utilizing a statute approach and comparative analysis, with secondary data collected through literature studies and analyzed qualitatively. The findings reveal that Law No. 1 of 2023 introduces substantial updates to the conditions resulting in the cessation of prosecutorial authority, differing from the arrangements under the 1946 Criminal Code. However, discrepancies in editorial formulation were identified between the new material criminal law and the formal criminal law as stipulated in the Criminal Procedure Code (KUHAP) of 1981 and the Draft Criminal Procedure Code of 2012. These inconsistencies indicate the need for harmonization to ensure uniformity and legal certainty within the criminal justice system. The implications of this study underline the necessity for legislative adjustments to align substantive and procedural criminal laws, thereby strengthening the coherence and effectiveness of criminal law enforcement in Indonesia.